Resiliensi Guru PAUD Ditinjau Dari Regulasi Emosi, Usia Dan Masa Kerja Pada Sekolah Inklusi - Alucyana; Yenni Yunita; Restu Nabila; Ria Safitri; Syarifah Fahriah (As-Sibyan)
This research examines the resilience of PAUD teachers in terms of emotional regulation, age and years of service in inclusive schools. The aim of this research is to analyze a teacher's regulation in terms of emotional regulation, the teacher's age and the teacher's length of service. This type of research is quantitative correlational. This approach is included in the correlational category because this research looks for whether there is a relationship between one variable and another variable and if there is a relationship then we look for the extent of the relationship between the variables. The variables in this research consist of Resilience and Emotional Regulation, Age and Years of Work. The sample in this research was 60 people. The data analysis method used is multiple regression. The research results found that emotional regulation, age and years of service had a significant effect on the resilience of PAUD teachers, 75.1% of the resilience of preschool teachers was influenced by emotional regulation, and 75.1% of age influenced the resilience of PAUD teachers in inclusive schools. It is hoped that future researchers will be able to develop the resilience of PAUD teachers in inclusive schools from other aspects.